Relationship between Maternal Mood Disorders and Dietary Intake of 3-Year-Olds - Minatsu Kobayashi; Kohei Ogawa; Naho Morisaki; Hisako Tanaka; Reiko Horikawa; Kevin Y. Urayama (Journal of Nutrition and Metabolism)
Maternal depression affects parenting and children’s early development, but its effect on dietary intake is unknown. While husbands’ involvement in parenting and having friends to talk to may reduce childcare stress, this has not been thoroughly studied. In this study, mothers were stratified by the presence or absence of mood disorders, and the effects of support from their husbands and friends on the dietary intake of their 3-year-old children were examined. This cross-sectional analysis included 920 mother-child pairs examined at the National Center for Child Health and Development in Japan. Dietary intake was assessed using a brief dietary history questionnaire, and physical measurements were taken when the children were 3 years old. The Kessler Psychological Distress Scale was used to screen for maternal mood disorders, 3 years after delivery. The presence or absence of the husband’s assistance with housework and childcare, mental support, and friends was obtained from a self-administered questionnaire when the child was 3 years old. Differences in the children’s physical measurements, energy, and food intake with the presence or absence of support for subjects with or without mood disorders were compared. Mothers with support from husbands or friends had significantly fewer mood disorders. Support from friends and family did not affect the children’s physical development and whether or not mothers had mood disorder symptoms. However, children’s vegetable intake was higher if mothers were supported. Children of mothers with mood disorders had a significantly higher vegetable intake and fruit intake, depending on the support from friends (P=0.046, P=0.037); thus, such support may increase children’s vegetable and fruit intake. The results of this study revealed the importance of supportive friends and family regarding childcare.